Effect of Piper Betle Nanospray 7% on Inflamation and IL-6 Levels in Postpartum Maternal Wounds : A Study in the Grobogan Regency Area, Central Java in 2025 - Fitriyaningsih, Erna Indah; Kumorowulan, Suryati; Suwondo, Ari; Rahayu, Sri; Hiyana TD, Christin (International Journal of Social Service and Research, 2025)
Postpartum second-degree perineal lesions are common and trigger an inflammatory response with an increase in IL-6. Suboptimal treatment risks prolonging the inflammatory process and inhibiting wound healing. Piper betle Linn is recognized as an herbal ingredient with anti-inflammatory potential; its nanospray formulation is believed to penetrate deeper layers of the skin, thereby accelerating wound healing. This study evaluated the effectiveness of a 7% betel leaf extract nanospray on the healing of perineal wounds in postpartum care. The study employed a true experimental design with a pretest-posttest control group, involving 40 respondents selected through stratified random sampling. The variables examined were the use of 7% betel leaf extract nanospray and the healing of grade II perineal wounds. Data analysis was conducted using the Kruskal-Wallis test and the Mann Whitney, followed by the Wilcoxon test. The findings demonstrated that administration of Piper betle Linn 7% nanospray extract significantly accelerated perineal wound healing, as measured by the REEDA scale (p < 0.05), with the majority of the intervention group (65%) exhibiting good healing. However, there was no significant difference in IL-6 levels between the intervention and control groups (p > 0.05). Piper betle Linn 7% nanospray extract is effective in accelerating the healing of grade II perineal wounds in postpartum mothers, as indicated by a decrease in REEDA scores, but does not significantly affect the reduction of IL-6 levels.